Experimental study of the influence of exhaust gas recirculation on heat transfer in the firedeck of a direct injection diesel engine. (1st December 2017) - Torregrosa, A.J.; Broatch, A.; Olmeda, P.; Salvador-Iborra, J.; Warey, A.
Highlights: Exhaust gas recirculation had a significant influence on in-cylinder heat transfer. The effect of exhaust gas recirculation was to reduce heat transfer. The strongest effect of exhaust gas recirculation was found in the firedeck center. Heat flux reductions up to 18% were observed locally. Carbon dioxide emission increased slightly but nitrogen oxides decreased largely. Abstract: Emissions control is a key topic for internal combustion engine development. One of the most widespread technologies to reduce the formation of nitrogen oxides is the recirculation of exhaust gas to the engine intake. Besides, carbon dioxide emissions from internal combustion engines can be reduced by increasing engine efficiency. A relevant factor for engine efficiency is heat rejection. The interaction between heat transfer and exhaust gas recirculation is not fully understood. In this paper, an experimental study is presented which aims to shed light on the influence of high pressure exhaust gas recirculation on heat transfer. Three operating points were analyzed. Heat flux was calculated at several locations of the firedeck from temperature measurements. The results showed that the influence of exhaust gas recirculation on heat transfer was significant. Reductions of heat flux up to 18% were observed. The largest reduction was found in the area near the center of the firedeck. To contextualize the findings in the framework of emissions reduction, the trade-off between nitrogen oxides and carbon dioxide was assessed for all test points.